Withasteroid B from D. metel L. regulates immune responses by modulating the JAK/STAT pathway and the IL‐17+RORγt+/IL‐10+FoxP3+ ratio. (4th August 2017) - Su, Y.; Wang, Q.; Yang, B.; Wu, L.; Cheng, G.; Kuang, H.
Summary: Datura metel L. is a medicinal herb that contains withasteroids and has a wide range of biological activities. We isolated seven withasteroids from the flowers of D. metel L and examined their ability to inhibit immune responses in vitro and in vivo . Among the withasteroids, withasteroid B2 exhibited the strongest inhibitory effect on immune responses comparing B2 with other isolated compounds from D. metel L., including suppressing the differentiation of CD4 + T cells by inhibiting the expression and production of T cell lineage‐specific master regulators and cytokines and directly suppressing the cytokine‐induced Janus kinase/signal transducer and activator of transcription (JAK/STAT) signalling pathways. In the interleukin (IL)‐23‐induced mouse ear model of skin disease, B2 repressed disease development by inhibiting the expression of proinflammatory mediators in murine ear skin. Moreover, B2 affected the maturation of dendritic cells (DCs) in vitro which, in turn, induced T cell differentiation with an increased regulatory T cell (Treg ) phenotype and decreased T helper type 17 (Th17) phenotype. This study provides new evidence that B2 might ameliorate chronic inflammatory skin diseases by suppressing pathogenic CD4 + T cell differentiation and the IL‐17 + retinoic‐acid‐receptor‐related orphan receptor gamma t (RORγt) + /IL‐10 + forkhead box protein 3 (FoxP3) + ratio. These findings suggest that B2 might mediate the therapeutic effects observed in psoriasis patients following treatment with D. metel L. Abstract : Among the isolated withasteroids, B2 exhibited the strongest inhibitory effect on immune responses in vivo and in vitro. This study provides new evidence that B2 might ameliorate chronic inflammatory skin diseases by suppressing pathogenic CD4+ T cell differentiation and the IL‐17+RORγt+/IL‐10+FoxP3+ ratio. These findings suggest that B2 might mediate the therapeutic effects observed in psoriasis patients following treatment with D. metel L.